PEMODELAN PROSES BISNIS REENGINEERING MENGGUNAKAN BUSINESS PROCESS MODELING NOTATION (STUDI KASUS PT AGUSTA DRYER) - Yudo Devianto; Corry Coriah Haerudin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Business process modeling is a way to understand, design and analyze a business process. The benefit of business process modeling is to help companies understand their business processes well, identify problems that may occur, develop, document and communicate them to all business stakeholders. So that companies can improve the performance of managing their business processes. The purpose of making a Business Process Model and Notation (BPMN) is to find out the business processes that occur at PT Agusta Dryer and minimize errors that often occur in the existing system at PT Agusta Dryer. The result of this research is that it is necessary to change the flow of business processes in terms of sales, service and purchase of goods.